Characterization of Mineral and Bone Metabolism Biomarkers in a Chinese Consanguineous Twin Family with Primary Hypertrophic Osteoarthropathy - Na Li; Yuhang Ma; Yun Jiang; Li You; Yunhong Huang; Yongde Peng; Xiaoying Ding; Li Zhao (International Journal of Endocrinology)
Purpose. Primary hypertrophic osteoarthropathy (PHO) is a rare, autosomal, recessive genetic disease characterized by digital clubbing, periostosis, and pachydermia. The underlying cause for the pathogenesis of this disease is a defect in prostaglandin E2 (PGE2) degradation, caused by mutations in HPGD or SLCO2A1. In this study, we describe the clinical characteristics, SLCO2A1 mutations, and bone metabolic markers of a PHO pedigree from a Chinese consanguineous twin family. Methods. Whole blood and urine samples were collected from all the family members. All the exons and exon-intron boundaries of the HPGD and SLCO2A1 genes were amplified using polymerase chain reaction (PCR) and sequenced. The biomarkers of mineral and bone metabolism, including calcium, phosphorus, parathyroid hormone (PTH), 25-hydroxyvitamin D (25(OH)D), bone Gla-protein (BGP), C-terminal telopeptide of type I collagen (β-CTX), and urinary calcium/creatinine ratio (Uca/Ucr) were detected. Results. A homozygous (nonsense) mutation in the SLCO2A1 gene (c.1807C >T/p.R603∗) was detected in the proband. Five heterozygous carriers were also identified among his relatives, including his twin brother. The serum BGP (225.5 ng/ml), β-CTX (4112 pg/ml), and Uca/Ucr (0.63) levels were significantly elevated, while the 25(OH)D (37.1 nmol/L) level was reduced in the proband. The proband’s twin brother displayed increased levels of β-CTX (901 pg/ml) and insufficiency of 25(OH)D (67.29 nmol/L), while the other heterozygous carriers only displayed 25(OH)D insufficiency. Conclusion. The patients with PHO displayed an active state of bone reconstruction. There may be a lack of vitamin D, accompanied by an increase in BGP and β-CTX levels. Heterozygous mutations of SLCO2A1 might lead to mild PHO.